Molecular detection of blaTEM, blaSHV,and blaCTX-M genes among Uropathogenic Escherichia coli isolated from cases with urinary tract infection in Erbil city-Iraq - K Ahmed, Kharman; A Hawezy , Aumed (Diyala Journal of Medicine, 2023)
Background: Urinary tract infections (UTIs) are the most popular type of diagnosed bacterial illness, and the most frequent cause of bacteria responsible for UTIs is Escherichia coli (E. coli). β-lactamases are the most frequent resistance for gram-negative bacteria to beta-lactam antibiotics, especially in E. coli. The number of patients infected by extended-spectrum β-lactamases (ESBLs) producing E. coli was rising and regarded as a significant global health problem. Objective: evaluate how frequently blaTEM, blaSHV, and blaCTX-M genes were detected in E. coli isolated from UTIs. Patients and Methods: We collected 54 midstream urine samples from patients with symptomatic UTIs, in all age groups, from the outpatient department in Erbil hospitals from October 1, 2021 to April 1, 2022 for the isolation of E. coli. All samples were analyzed for the detection of blaTEM, blaSHV, and blaCTX genes using the polymerase chain reaction (PCR) method. Results: Most of the samples were taken from females (61.11%); according to their ages, they were divided into two groups, and most of the samples (74.07%) were taken from patients below 40 years old. PCR testing for all ESBL-producing E. coli isolate samples revealed that 16S rRNA 797 was the most frequently detected gene in all analyzed samples (100%), while it was less frequently detected in blaCTX 585 (48.15%). Conclusion: Colonization with S. aureus and MRSA inversely correlated with younger This found that elevated ESBL genes in E. coli isolated from symptomatic UTIs in our community increase the risk of possible resistance.